FPGA Implementation of a Chaotic Quadratic Map for Cryptographic Applications - Oğraş, Hidayet; Türk, Mustafa (Fırat University, 2017)
A hardware implementation of a quadratic map through FPGA platform is proposed in this paper. Firstly, achaotic quadratic map is modeled by using Matlab/Simulink programming and then implemented into the FPGA(Field Programmable Gate Array) to be used for key generation for cryptographic applications. When thequadratic map is in chaotic mode, its output is unpredictable and aperiodic. Besides this, the map has a uniformoutput distribution and sufficient randomness. These characteristics make the chaotic quadratic map a suitablekey generator for cryptography. This paper also reveals the successful real-time implementation of the quadraticmap using FPGA for practical applications. Experimental results confirm that the feasibility of the quadratic mapis verified under a digital hardware environment.